METODE IJTIHAD IMAM ABU HANIFAH - Mardjudo, Abd. Basyir (State Institute of Islamic Studies (IAIN) Palu, 2006)
Abu Hanifah is a predominant figure of school of Islamic law in Islam. He is a founder of Hannafite school of Islamic law who employees reason for his legal reasoning. It is this that makes him different from other founders of schools of Islamic law who uses riwayah with the emphasis on the chronology of nash as the main source of their ijtihad.. Method of ra’yu intended in this school of Islamic law that of qiyas that analogizes something having no naskh with that having naskh since the two have similarity in the respect of their legal arguments. In this respect, the emphasis is put on four pillars, namely al-ashl, al-far’a, hukm al-ashl and illat.Kata Kunci: Abu Hanifah, ijtihad, ahl al-ra’yu, ahl al-riwayah, qiyas, istishan